Common influences of non-competitive NMDA receptor antagonists on the consolidation and reconsolidation of cocaine-cue memory - Alaghband, Yasaman (2012)
RATIONALE: Environmental stimuli or contexts previously associated with rewarding drugs contribute importantly to relapse among addicts, and research has focused on neurobiological processes maintaining those memories. Much research shows contributions of cell surface receptors and intracellular signaling pathways in maintaining associations between rewarding drugs (e.g., cocaine) and concurrent cues/contexts; these memories can be degraded at the time of their retrieval through reconsolidation interference. Much less studied is the consolidation of drug-cue memories during their acquisition. OBJECTIVE: The present experiments use the cocaine conditioned place preference (CPP) paradigm in rats to directly compare, in a consistent setting, the effects of N-methyl-D-aspartate (NMDA) glutamate receptor antagonists MK-801 and memantine on the consolidation and reconsolidation of cocaine-cue memories. METHODS: For the consolidation studies, animals were systemically administered MK-801 or memantine immediately following training sessions. To investigate the effects of these NMDA receptor antagonists on the retention of previously-established cocaine-cue memories, animals were systemically administered MK-801 or memantine immediately after memory retrieval. RESULTS: Animals given either NMDA receptor antagonist immediately following training sessions did not establish a preference for the cocaine-paired compartment. Post-retrieval administration of either NMDA receptor antagonist attenuated the animals' preference for the cocaine-paired compartment. Furthermore, animals given NMDA receptor antagonists post-retrieval showed a blunted response to cocaine-primed reinstatement. CONCLUSIONS: Using two distinct NMDA receptor antagonists in a common setting, these findings demonstrate that NMDA receptor-dependent processes contribute both to the consolidation and reconsolidation of cocaine-cue memories, and they point to the potential utility of treatments that interfere with drug-cue memory reconsolidation.